Razumevanje in odnos do telesa pri uršulinkah - Župevc, Katarina (Etnolog. Nova vrsta (Ljubljana), 2007)
Changing attitudes to the body can be traced in different temporal as well as spatial contexts. The body as the fi rst level of interaction in social contacts has a symbolic meaning in present-day society. The contemporary emphasis on corporality and the desired shape and condition of the body has a strong infl uence on the conception people have of their own body, and this isalso connected with the behaviour towards their body. The female body is particularly exposed to these trends, because great importance is attributed to it in shaping a womanćs identity based on refl ections in the environment. Is it possible then to refer to a monastic community as an environment with a specifi c attitude to the body?
Keywords: Slovenci; Slovenes; verovanje; redovnice; uršulinke; telo; nadzor; identiteta